PENGARUH BIMBINGAN PRIBADI-SOSIAL TERHADAP PENGEMBANGAN PERCAYA DIRI SISWA DI KELAS XI SMA NEGERI 6 SURAKARTA TAHUN PELAJARAN 2017/2018 - Wibowo, Budi Ari; Sri Suryani, Hera Heru (UNIVERSITAS SLAMET RIYADI, 2017)
ABSTRACTThe population in this study were students of class XI of SMA Negeri 6 Surakarta in the academic year 2017/2018 in class 304. From 11 classes the number of members used 2 classes as a sample where class XI Ips 5 as a trial and class Mipa 1 as medical assistance. Thus the sampling technique in this study is Simple Random Sampling. Data collection techniques in this study used a questionnaire, observation and documentation. The questionnaire method is used to collect data about self-confidence, the observation method is used to obtain low self-confidence characteristics in students in the school environment and learning activities, while the registrant method is used to obtain activity data. Based on the data analysis, data analysis techniques with t-test. It can be concluded that there is a good social assistance for the development of student confidence in class XI of SMA Negeri 6 Surakarta in 2017/2018 Academic Year. This is evidenced by t arithmetic = 13,043 consulted with t table with d.b = (N-1) = (27-1) = 26 in the significance level of 5% and 1%. So it can be calculated t arithmetic greater than t table or 2,056 <13,043> 2,779. Thus the hypothesis that reads